Analysis of the Role of Sharia Financing Product Innovation and Compliance with Profit Sharing Principles in Increasing the Attractiveness of Sharia Banks for MSMEs in Bandung City - Pahrijal, Rival; Rafik, Zainur (Westscience Press, 2026)
This study examines the role of sharia financing product innovation and compliance with profit-sharing principles in enhancing the attractiveness of sharia banks for micro, small, and medium enterprises (MSMEs) in Bandung City. MSMEs play a crucial role in the local economy but often face constraints in accessing suitable financing. Sharia banks offer an alternative financing model based on ethical values and profit-sharing mechanisms; however, their attractiveness depends on both product innovation and consistent adherence to sharia principles. This research adopts a quantitative approach using primary data collected from 150 MSME actors through a structured questionnaire measured on a five-point Likert scale. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) version 3. The results show that sharia financing product innovation has a positive and significant effect on the attractiveness of sharia banks. Furthermore, compliance with profit-sharing principles demonstrates a stronger positive influence, indicating that transparency, fairness, and authentic sharia implementation are critical in building MSME trust and preference. The findings suggest that sharia banks should integrate continuous product innovation with strict adherence to profit-sharing principles to enhance competitiveness and strengthen long-term relationships with MSMEs. This study contributes to the empirical literature on Islamic banking and provides practical implications for sharia bank management in designing MSME-oriented financing strategies.